Blasting and Passivation Treatments for ASTM F139 Stainless Steel for Biomedical Applications : Effects on Surface Roughness, Hardening, and Localized Corrosion - Lemos Barboza, Adriana Lucila (2014)
Due to the combination of good biofunctionality and biocompatibility at low cost, AISI 316 low carbon vacuum melting (LVM) stainless steel, as considered in ASTM F139 standard, is often the first choice for medical implants, particularly for use in orthopedic surgery. Proper surface finish must be provided to ensure adequate interactions of the alloy with human body tissues that in turn allows the material to deliver the desired performance. Preliminary studies performed in our laboratory on AISI 316LVM stainless steel surfaces modified by glass bead blasting (from industrial supplier) followed by different nitric acid passivation conditions disclosed the necessity to extend parameters of the surface treatments and to further consider roughness, pitting corrosion resistance, and surface and subsurface hardening measurements, all in one, as the most effective characterization strategy. This was the approach adopted in the present work. Roughness assessment was performed by means of amplitude parameters, functional parameters, and an estimator of the fractal dimension that characterizes surface topography. We clearly demonstrate that the blasting treatment should be carried out under controlled conditions in order to obtain similar surface and subsurface properties. Otherwise, a variation in one of the parameters could modify the surface properties, exerting a profound impact on its application as biomaterial. A passivation step is necessary to offset the detrimental effect of blasting on pitting corrosion resistance.